The Autonomous Pinger Unit of the Acoustic Navigation Network in EnEx-RANGE: an autonomous in-ice melting probe with acoustic instrumentation. Issue 84 (7th April 2021) - Weinstock, Lars Steffen; Zierke, Simon; Eliseev, Dmitry; Linder, Peter; Vollbrecht, Cornelius; Heinen, Dirk; Wiebusch, Christopher
Abstract: The Autonomous Pinger Unit (APU) is an electro-thermal drill with acoustic instrumentation developed for the project EnEx-RANGE in view of a future space mission for the sub-surface exploration of Saturn's moon Enceladus. A main goal is the development of navigation technology for an acoustic guidance system allowing maneuvering a probe through glacial ice. In total 13 APUs were built and tested in terrestrial analog scenarios on alpine glaciers. The APUs form a spatially distributed network that defines a system of reference for the navigation of the maneuverable probe to a point of interest. The APUs have a novel melting head, slow control systems, and a modern system-on-chip (SoC) module that controls the probe and processes the recorded data. The APUs use acoustic emitters and receivers to measure the transit time of acoustic signals between them, allowing for the position reconstruction of all APUs by trilateration. Several auxiliary sensors monitor the internal state of the probe and assist the position estimation. With this instrumentation, the APUs have the ability of dynamically optimizing themselves within the network by changing their position. This paper gives an overview of the developed APU hardware and presents performance results from the field tests.